2010
DOI: 10.1210/en.2010-0195
|View full text |Cite
|
Sign up to set email alerts
|

Central Injection of the Stable Somatostatin Analog ODT8-SST Induces a Somatostatin2 Receptor-Mediated Orexigenic Effect: Role of Neuropeptide Y and Opioid Signaling Pathways in Rats

Abstract: Somatostatin and octreotide injected into the brain have been reported to modulate food intake. However, little is known regarding the underlying mechanisms. The stable oligosomatostatin analog, des-AA 1,2,4,5,12, ]-somatostatin (ODT8-SST), like somatostatin, binds to all five somatostatin receptors (sst 1-5 ). We characterized the effects of ODT8-SST injected intracerebroventricularly (icv) on food consumption and related mechanisms of action in freely fed rats. ODT8-SST (0.3 and 1 g per rat, icv) injected du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
134
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(147 citation statements)
references
References 81 publications
9
134
1
3
Order By: Relevance
“…Rats had free access to food and water before and during the experiment. Behavior was assessed manually and simultaneously in 4 rats/investigator, as described in our previous studies (50,51,53). This method requires a time-sampling technique by two investigators, who performed all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats had free access to food and water before and during the experiment. Behavior was assessed manually and simultaneously in 4 rats/investigator, as described in our previous studies (50,51,53). This method requires a time-sampling technique by two investigators, who performed all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…This has been used in rats before (15,31,39,49) and was established recently for the use in mice (21,52). To investigate the specificity of the observed effects on feeding behavior, other behavioral parameters, such as grooming and locomotor activity, were assessed as established originally by Antin et al (1) and in our previous studies (50,53).…”
Section: ·Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations on the influence of brain CRF signaling pathways in the tail-pinch feeding response have led to contradictory results (21,46). By contrast, the possible involvement of interconnected brain orexigenic signalings namely those involving neuropeptide Y (NPY)/Y 1 receptors (49,54) or recently demonstrated somatostatin receptor 2 (sst 2 )/NPY 1 (57) have not been explored. With regard to the sst 2 , we recently showed that intracerebroventricular (icv) injection of a sst 2 agonist in satiated rats induces a rapid and robust food intake response through activation of NPY 1 receptors (57).…”
mentioning
confidence: 99%
“…In the present study, we first investigated the molecular substrates and neurocircuits involved in the acute 5-min mild tail pinch-induced feeding response focusing on the orexigenic pathways, namely, the ghrelin-NPY-opioid circuit and sst 2 pathways (54,57,66). This was achieved using selective antagonists of NPY 1 , BIBP-3226 (38), and sst 2 receptor S-406-028 (9) injected intracerebroventricularly and the -opiate receptor antagonist naloxone along with the measurement of circulating ghrelin levels and blood glucose.…”
mentioning
confidence: 99%